2015
DOI: 10.1080/01616846.2015.1000783
|View full text |Cite
|
Sign up to set email alerts
|

Collection Development Policies in Public Libraries in Australia: A Qualitative Content Analysis

Abstract: The role that public library collection development policies play in guiding selectors and informing users has been promoted as a pillar of good professional practice. While these policies purport to open up the methods and the criteria used in selection so as to promote transparency and a sense of professional objectivity, how they actually are developed and put into practice has remained largely implicit in the research literature. This analysis revealed that policies tended to focus on local issues and rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
5
0
1
Order By: Relevance
“…This research was conducted in two parts, exploring both collection policies and item metadata. The first part uses qualitative content analysis to identify common themes in collection policies, providing insight into how librarians make decisions around selection and evaluation of collection materials (Kelly, 2015). This provides insight into how selection criteria creates opportunities or barriers for including locallyauthored items.…”
Section: Methodsmentioning
confidence: 99%
“…This research was conducted in two parts, exploring both collection policies and item metadata. The first part uses qualitative content analysis to identify common themes in collection policies, providing insight into how librarians make decisions around selection and evaluation of collection materials (Kelly, 2015). This provides insight into how selection criteria creates opportunities or barriers for including locallyauthored items.…”
Section: Methodsmentioning
confidence: 99%
“…Di dalamnya berisikan acuan berbentuk dokumen atau pernyataan resmi secara tertulis mengenai prinsip, kriteria dan keputusan mengenai seleksi koleksi perpustakaan. Kebijakan pengembangan koleksi juga menjadi penilaian dalam mengukur sedalam apa koleksi yang dimiliki, prioritas/urgensitas koleksi yang dibutuhkan dalam memenuhi semua kebutuhan penggunanya hingga pengadaan yang akan dilakukan (Kelly, 2015). Selain menjadi parameter, kebijakan pengembangan koleksi juga menjadi kerangka kerja bagi para staf perpustakaan di dalamnya.…”
Section: Metode Penelitianunclassified
“…The analysis of public library collection-oriented policies has not been extensive: Scanlon’s (2012) study included those of 28 Scottish public libraries, Kelly’s (2015) study included those of 7 Australian public libraries, while Osborne’s (2018) study examined 5 from North Carolina public libraries, but none of these focus on deselection. Burke’s (2016) study of a random national selection of US public libraries found that most had websites with a limited amount of administrative information, but that links to any library policies were much less frequent.…”
Section: The Weeding Policies Problematicmentioning
confidence: 99%